Extraction of dynamic avalanche during IGBT turn off. (September 2017) - Geissmann, Silvan; Michielis, L. De; Corvasce, Ch.; Rahimo, M.; Andenna, M.
Abstract: When IGBTs are switched with high dV/dt at high currents, dynamic avalanche occurs. Under certain conditions, this phenomenon is known to potentially degrade certain IGBT architectures. An investigation of the possible degradation of our planar IGBTs was started. This paper presents a method to extract the current (and consequently charge and energy) due to dynamic avalanche from measured turn off waveforms. The method is checked with TCAD simulations and applied to an accelerated stress test on two different device designs. Highlights: A method for extracting dynamic avalanche from a turn off waveform is proposed. The extraction is checked by applying it to simulation data. Degradation on a test structure is correlated to extracted data.